PENGELOLAAN BAITUL MAAL PADA BAITUL MAAL WA TAMWIL (BMT) DI KOTA PEKALONGAN - Agus Fakhrina (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2015)
This research was aimed to know whether the interest based-banking system still shadow the sharia based-banking system in the light of that the former operate in a banking industry dominate by interest system.to proof whether it is true or not, it is necessary to do a research that questions whether interest rate of credit and deposit of conventional bank influence margin rate of murabahah finance of Islamic bank in Indonesia. The result showed that in a banking industry environment dominated by interest system, Islamic bank have not yet release from the old system. This is proven by that interest rate of credit and deposit of conventional bank has significance influence to margin rate of Islamic bank Indonesia, either partially or simultaneously, with determination coefficient 53.1%. It means that the contribution of those both variables (interest rate of credit and deposit simultaneously) to margin rate of murabahah is 53.1%. The rest (46.9%) is influenced by other factors.